Patterns of Islamic Religion Development for Juvenile Convicts at Special Child Development Institute (LPKA) Class I Martapura - Nuwairah, Khaleyda Mariza; Alpiandi, Alpiandi (Al-Aulad: Journal of Islamic Primary Education, 2024)
Adolescence is a process of transition of a human being from childhood to adulthood. In this phase, there are many behavioral deviations committed by a person, so that religious education, especially Islam, is needed to overcome these various deviations. The Martapura Class I Special Development Institutions for Children is an institution that focuses on providing guidence to adolescents who are concidered problematic according to lawsuits so that one day they can recover and obtain religious provisions to be brought into society. The aim of this research is to find out the pattern of fostering the Islamic religion for juvenile convicts at the institution, including the development of worship, faith and morals. This research is a type of field research with a qualitative descriptive method. The research subjects here are the mentors and three youths assisted at the institutions, while the object of research is the pattern of Islamic religious development for juvenile convicts. The data collection techniques that the authors use are interviews, documentation, and observation which are the processed through reduction, presentation, data verification and conclusion. Based on the data found, the pattern of fostering Islam for juvenile convicts at the Children’s Special Development Institution is worship coaching that focuses on learning the Koran, creed, prayer, dhikr, tahlilan. Development of aqidah that focused on learning the pillars of faith and monotheism. Moral development aimed at forming noble behavior.